New Art : at the Tate Gallery 1983 - Compton, Michael (London : Tate Gallery, 1983)
Ahearn, John ; Armajani, Siah ; Art & Language ; Artschwager, Richard ; Baselitz, Georg ; Basquiat, Jean Michel ; Beuys, Joseph ; Boisrond, François ; Borofsky, Jon ; Brauntuch, Troy ; Brisley, Stuart ; Brus, Günter ; Buren, Daniel ; Burgin, Victor ; Burton, Scott ; Byars, James Lee ; Chia, Sandro ; Clemente, Francesco ; Combas, Robert ; Cox, Stephen ; Cragg, Tony ; Craig Martin, Michael ; Cucchi, Enzo ; Dahn, Walter ; Deacon, Richard ; Dennis, Donna ; Dimitrijevic, Braco ; Disler, Martin ; etc.
New Art at the Tate Gallery 1983, The Tate Gallery, London, 14 September - 23 October 1983
boek